Sertifikasi Makanan Halal Untuk Meningkatkan Daya Saing UMKM di Desa Paciran - Aini Tsalsa Maulidhina; Basya, Maziyah Mazza Basya (Jurnal Bilal: Bisnis Ekonomi Halal, 2024)
This research aims to analyze the impact of halal certification on the competitiveness of SMEs in Paciran Village. The research method used is a qualitative approach with a case study on three SMEs: Dimsum Sultan, BakerynChi, and Jajanal, involving 10 consumers. Data were collected through in-depth interviews and direct observation. The results show that halal certification increases consumer trust, expands market access, and boosts sales, particularly for certified SMEs. However, small SMEs face challenges regarding the costs and application process of halal certification. Consumers in Paciran Village tend to prefer halal-certified products, although quality and price remain key factors in purchasing decisions. This study concludes that halal certification plays a crucial role in enhancing the competitiveness of SMEs in broader markets.